2009
DOI: 10.1016/j.rgg.2009.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Petromagnetic parameters of bottom sediments as indicators of the climatic and environmental changes in the central zone of the Sea of Okhotsk during the last 350 kyr

Abstract: Bottom sediments from the central zone of the Sea of Okhotsk were preliminarily dated. The petromagnetic parameters of two groups of samples formed at cold and warm climatic stages were studied. Warm oxygen isotopic stages and substages were characterized by the coexistence of pseudo-single-domain allogenic magnetite and predominant magnetite and greigite (pyrrhotite) grains subject to biologic control. At cold stages, sediments containing a mixture of pseudo-single-domain and multidomain terrigenous magnetite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 24 publications
4
28
0
Order By: Relevance
“…core SO-201-12KL (hereinafter 12KL) (Max et al, 2012(Max et al, , 2014. Using robust age controls, we establish a tight linkage between the centennial events with higher productivity in the NW Pacific and the sub-interstadial strengthened East Asian summer monsoon (EASM) expressed in cave stalagmite δ 18 O records.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…core SO-201-12KL (hereinafter 12KL) (Max et al, 2012(Max et al, , 2014. Using robust age controls, we establish a tight linkage between the centennial events with higher productivity in the NW Pacific and the sub-interstadial strengthened East Asian summer monsoon (EASM) expressed in cave stalagmite δ 18 O records.…”
Section: Introductionmentioning
confidence: 86%
“…These model and proxy studies suggested either in-phase relationships of deglacial variability between the North (N) Atlantic and NW Pacific (Caissie et al, 2010;Chikamoto et al, 2012;Kienast and McKay, 2001;Seki et al, 2002) or out-of-phase responses (Gebhardt et al, 2008;Sarnthein et al, 2006). The in-phase relationship has been attributed to rapid atmospheric teleconnections in the Northern Hemisphere on a decadal timescale (Max et al, 2012). The winter Arctic Oscillation (AO), which resembles the North Atlantic Oscillation, directly influences the surface air temperature and sea level pressure over the region northwards of 35 • N in East Asia (Sung et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In general, the IRD carried by the terrigenous fraction is an assorted mixture of gravel, sand, silt and clay size materials (Gorbarenko et al, 2002). However, the defined clastic diameter of terrigenous materials considered as IRD is dominantly of sand size between 63 μm and 2000 μm (Bigg et al, 2008;Gorbarenko et al, 2008;Malakhov et al, 2009), whereas that for drop-stones should be larger than sand, i.e. N2000 μm Selvaraj et al, 2012).…”
Section: Introductionmentioning
confidence: 99%